Dynamic Logic of Propositional Assignments: A Well-Behaved Variant of PDL - Balbiani, Philippe; Herzig, Andreas; Troquard, Nicolas (2013 28th Annual ACM/IEEE Symposium on Logic in Computer Science, 2013)
We study a version of Propositional Dynamic Logic (PDL) that we call Dynamic Logic of Propositional Assignments (DL-PA). The atomic programs of DL-PA are assignments of propositional variables to true or to false. We show that DL-PA behaves better than PDL, having e.g. compactness and eliminability of the Kleene star. We establish tight complexity results: both satisfiability and model checking are EXPTIME-complete.